(untitled) (Confluenţe Bibliologice, 2022)
The article describes, in a concise manner, the activity of the Romanian Orthodox Patriarchate of Chernivtsi in the 20-30s of the 20th century, as well as the events of 1940, followed by the persecution of the faithful.